THE ANIMATED SELF-PORTRAIT AS A GENRE FORM OF AUTOBIOPICS / АНИМАЦИОННЫЙ АВТОПОРТРЕТ КАК ЖАНРОВАЯ ФОРМА АВТОБАЙОПИКИ - KRIVULYA NATALIA G. / КРИВУЛЯ Н.Г. (Наука телевидения, 2019)
The article explores an autobiopic, one of the forms of a biographical film. It is defined as a screen artwork, an author’s narration, based on events, selected by the author from the assortment of facts from his/her biography. The article gives definitions of an autobiographic film and defines the basic principles of the narration structure. Such genres of the autobiographic film as a reminiscence, a diary, travel notes and a self-portrait, the central subject of the article, are described. A specific feature of an animated selfportrait, that separates it from other films in the animated biopic genre is the author’s strive for self-identification, self-realization, self-identification and self-reflection, in other words the author’s addressing his/her inner and outer self. Unlike autobiographic reminiscences or diary films, where events are lying at the core of the narration, the story in the self-portrait films is of lower importance. For their creation the authors use presentation strategies, there is no temporal distance from the event, this is always what is happening “here and now.” The author of a self-portrait film is not so much trying to tell a story about himself/herself, as to present his/her identity, his/her other selves or possible selves. In contrast to an autobiographic documentary film, an animated self-portrait is an image of an idea rather than an image of a given fact. In this aspect the self-portrait film is viewed as a communication form, in which the dialog occurs between myself-Perceived, myself-seen-as-Another-Me and myself-Thinking or self-Realizing. The occurring dialogue is based on the themes of conflict and collision of different notional attitudes directed towards processing of emotional and intellectually significant meanings by the subject. Unlike portrait films, self-portrait films are always created to fulfil one’s personal ambitions, desires and longings. Therefore, on one hand the animated self-portrait could be viewed as a form of an optical narcissism and on the other hand, as a form of optical exhibitionism. A reflected image is replaced by a hypothetical image. The created image corresponds to the self, the author sees or wants to see. The main feature of the self-portrait genre is the specific form of emotional and artistic self-analysis in a broad context, including a web of the author’s connections with historic, social/cultural, and everyday environment. For the analysis of the animated self-portrait a cross-discipline approach was applied, allowing connection of the autobiopic genre with painting and literature traditions. The article brings to a spotlight the origins of the animated self-portrait and discusses its development in the future.